Meningkatkan Kemampuan Membaca Intensif Dengan Metode Cooperative Integrated Reading Composition Pada Peserta Didik : Improving Intensive Reading Skills With The Cooperative Integrated Reading Composition Method For Students - Sophia, Eva (Neraca: Jurnal Pendidikan Ekonomi, 2023)
The subjects of this study were 32 class VIII 9 students of SMP Negeri 2 Palangka Raya, consisting of 16 boys and 16 girls. The ability to read intensively to find main ideas using the Cooperative Integrated Reading and Composition method has been shown to increase. The results of the knowledge test on the initial conditions of the class average score from 70 rose to 79 in cycle I, then rose again to 84 in cycle II. Mastery learning results of the knowledge test, initial conditions of 10 students or 31% increased to 23 students or 72%, in cycle I. Cycle II increased again by 29 students or 91%. The results of the intensive reading skills test to find the main idea of the initial condition of the class average acquisition of 60 with completeness of 4 students or 13%. Cycle I average class of 76 with the number of students completing as much as 17 or 53%. Cycle II the average class score was 82 with the number of students completing 29 students or 91%. The positive behavior of students after participating in intensive reading skills learning to find the main ideas has also increased. Based on the results of observations of student behavior, the percentage of the first cycle was 51%, in the second cycle it increased to 81%. Big increase of 30%. The results of this study concluded that the Cooperative Integrated Reading and Composition method can improve intensive reading skills to find the main ideas in reading texts and positive behavior in student learning.